Climate adaptation of biodiversity conservation in managed forest landscapes. Issue 3 (29th November 2021) - Hylander, Kristoffer; Greiser, Caroline; Christiansen, Ditte M.; Koelemeijer, Irena A.
Abstract: Conservation of biodiversity in managed forest landscapes needs to be complemented with new approaches given the threat from rapid climate change. Most frameworks for adaptation of biodiversity conservation to climate change include two major strategies. The first is the resistance strategy, which focuses on actions to increase the capacity of species and communities to resist change. The second is the transformation strategy and includes actions that ease the transformation of communities to a set of species that are well adapted to the novel environmental conditions. We suggest a number of concrete actions policy makers and managers can take. Under the resistance strategy, five tools are introduced, including: identifying and protecting forest climate refugia with cold‐favored species; reducing the effects of drought by protecting the hydrological network; and actively removing competitors when they threaten cold‐favored species. Under the transformation strategy, we suggest three tools, including: enhancing conditions for forest species favored by the new climate, but currently disfavored by forest management, by planting them at suitable sites outside their main range; and increasing connectivity across the landscape to enhance the expansion of warm‐favored species to sites that have become suitable. Finally, we suggest applying a landscape perspective and simultaneously managing for both retreating and expanding species. The two different strategies (resistance and transformation) should be seen as complementary ways to maintain a rich biodiversity in future forest ecosystems. Abstract : Article impact statement : The resistance and transformation strategies should be used in parallel when implementing climate adaptation for biodiversity conservation. Abstract : Adaptación Climática de la Conservación de la Biodiversidad en Paisajes Forestales Gestionados Resumen: La conservación de la biodiversidad en los paisajes forestales gestionados necesita complementarse con estrategias nuevas debido a la amenaza del cambio climático acelerado. La mayoría de los marcos de trabajo para la adaptación de la conservación de la biodiversidad ante el cambio climático incluye dos estrategias principales. La primera es la estrategia de resistencia, la cual se enfoca en acciones para incrementar la capacidad de las especies y comunidades para resistir el cambio. La segunda es la estrategia de transformación e incluye acciones que facilitan la transformación de las comunidades a un conjunto de especies que están bien adaptadas a las nuevas condiciones ambientales. Sugerimos un número de acciones concretas que los gestores y los formuladores de políticas pueden tomar. Bajo la estrategia de resistencia, introducimos cinco herramientas, incluyendo: identificación y protección de los refugios climáticos forestales con especies favorecidas por el frío, reducción de los efectos de la sequía mediante la protección de la red hidrológica y extirpación activa de los competidores cuando amenacen a las especies favorecidas por el frío. Bajo la estrategia de transformación, sugerimos tres herramientas, incluyendo: mejorar las condiciones para las especies forestales favorecidas por el nuevo clima pero actualmente desfavorecidas por la gestión forestal, mediante su siembra en sitios adecuados fuera de su distribución principal e incrementando la conectividad en el paisaje para incrementar la expansión de las especies favorecidas por el calor hacia sitios que se han vuelto más adecuados. Finalmente, sugerimos aplicar una perspectiva de paisaje y gestionar simultáneamente tanto para las especies en retirada y en expansión. Las dos estrategias diferentes (resistencia y transformación) deberían considerarse como maneras complementarias para mantener una biodiversidad rica en los ecosistemas forestales del futuro.